Concordance Rate Between Examination of EGFR Mutation Blood Plasma Sample (ctDNA) With Citological/Histopathological Sample in Adenocarcinoma Lung Cancer - Dian Utami Wulaningrum; Ana Rima Setijadi; Suradi Suradi (Indonesian Society of Respirology (ISR), 2020)
Background: Most adenocarcinoma lung cancer which is found at an advanced stage with cytology / histopathological samples is hardly available. Examination of EGFR mutations in ctDNA blood plasma sampling is simpler and easier, which also can be used as predictive and prognostic markers in non-small cell carcinoma lung cancer patients. The purpose of this study is to determine and analyse the degree of compatibility between examination of EGFR mutations by blood plasma (ctDNA) samples with the examination of cytology / histopathological EGFR mutations in adenocarcinoma lung cancer. Methods: Diagnostic test research, by taking medical records of patients with adenocarcinoma lung cancer from January to September 2019 at Dr. Moewardi Surakarta, who was examined by EGFR mutations in cytology / histopathology and ctDNA samples. Result: The Subjects of this study were 73 patients with adenocarcinoma lung cancer. The level of compatibility of ctDNA with EGFR mutations in cytology / histopathology samples was categorized as moderate and statistically significant (Kappa = 0.459; p = 0.000). Conclusion: The level of concordance between the examination of EGFR mutations with blood plasma samples (ctDNA) with the examination of EGFR mutations in cytology / histopathology samples was moderate and statistically significant.